Assessment of bacterial inoculant formulated with Paraburkholderia tropica to enhance wheat productivity - Bernabeu, Pamela Romina (2018)
Paraburkholderia tropica is an endophytic nitrogen-fixing bacterium isolated from the rhizosphere, rhizoplane, and internal tissues of sugarcane and corn plants in different geographical regions. Other plant-growth-promoting abilities, such as phosphate solubilization and antifungal activity, have also been reported for this bacterium. With an aim at investigating the potential use of P. tropica as an inoculant for improving the performance of wheat crop, in this work we evaluated an experimental inoculant formulated with P. tropica MTo-293 with respect to root colonization, the practical aspects of its application, and the effects under field conditions when applied to wheat seeds. Bacterial colonization was monitored by culture dependent techniques and the wheat yield determined by quantifying the total grain production in two different seasons. Rhizoplane and endophytic colonization in wheat roots was achieved efficiently (on average, 8 and 4 log colony-forming units/g fresh weight, respectively) even at relatively low concentrations of viable bacteria in the inoculum under controlled conditions. P. tropica was compatible with a widely used fungicide, maintained viability for 48 h once applied to seeds, and was also able to colonize wheat roots efficiently. Furthermore, we were able to formulate an inoculant that maintained bacterial viability for relatively long time periods. Preliminary field assays were realized, and even though the average yields values for the inoculated treatments remained above the uninoculated ones, no significant effects of inoculation were detected with or without fertilization. The correct physiologic behavior of P. tropica suggests the necessity to continue with field experiments under different conditions.